Agile resilience for the future human resource management profession: Methodologies, strategies, and best practices - Isabirye, AK; Mampuru, MP (Edelweiss Applied Science and Technology, 2025)
The swiftly changing business environment of the 21st century requires a transformation in Human Resource Management (HRM) towards a framework based on ’Agile Resilience.’ This theoretical article offers a thorough qualitative literature assessment, drawing information from esteemed databases including JSTOR, Google Scholar, ProQuest, and Wiley Online Library, to examine how Agile Resilience might transform the future of HRM to address essential organizational needs. We present a literature-based comprehensive framework designed to improve organizational agility, responsiveness, and resilience in the face of growing complexities. Critical segments of the article explore the necessity of Agile Resilience, analyzing the requirement for adaptation to fluctuating business landscapes and pinpointing current issues encountered by HRM experts. We examine how utilizing agile approaches can enhance responsive HR practices, the importance of developing a culture of agile resilience within HR teams, and the critical function of technology in enabling agile HR operations. The essay emphasizes the need to redefine HR competencies for the agile era and presents concrete ideas and best practices for implementing Agile Resilience in HR services. Our findings highlight the critical necessity for organizations to cultivate adaptive resilience to effectively traverse a constantly evolving environment. This research comprehensively delineates its theoretical and practical ramifications, as well as its limitations and suggestions for future inquiry. In conclusion, we emphasize the essential function of Agile Resilience in maintaining the future significance and effectiveness of the HRM profession, promoting a proactive adoption of adaptable solutions to attain sustainable organizational success.